The Buddhists in Australia - Adam, Enid L. (Enid Lilian), 1936-; Hughes, Philip J.; Australia. Bureau of Immigration, Multicultural and Population Research (Canberra : Australia Govt. Pub. Service, 1996)
Provides an account of the early development of Buddhism in Australia and describes the way it is practiced and organized in Australia. It outlines how recent immigration from Asia has resulted in the proliferation of Buddhist communities in the light of 1991 Census data and includes an examination of contempory Australian Buddhists.
Series General Editor: Philip J. Hughes.
"Bureau of Immigration, Multicultural and Population Research"
Includes tables.
Bibliography: p. 70-71.
Keywords: Buddhists -- Australia; Buddhists -- Australia -- Census, 1991.; Buddhism -- Australia; Buddhism -- Australia -- History